The new Catalan nationalism - Rivero, Ángel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, I have shown how Catalan nationalism mutated in the last years. Since 1979 Catalonia enjoyed unprecedented political self-government, however, its political autonomy was not enough for the independence movement. With the economic crisis of 2008, they declared that the time of independence has finally arrived, and in 2017 a bizarre independence that lasted a few seconds was proclaimed.
Keywords: nationalism; Catalonia; populism; antagonism; real democracy; secession; constitution